esain Rumah Untuk Kaum Marjinal di Kota Kendari Provinsi Sulawesi Tenggara - Umar, Muhammad Zakaria (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
In Kendari City, growing and developing public housing funded by the Bank. However, housing tends to be still difficult to reach by the lower classes of society. The lower classes of society such as herbalists, motorcycle taxi drivers, construction workers, scavengers, street vendors, and so on. In general, the lower class of society resides in rented houses. This research is important as follows: (a) to provide alternative prototypes of simple houses for the lower classes of society; (b) to make prototypes of low-cost homes; (c) to assist the government and private developers in providing alternative solutions to housing for the lower classes of society; (d) to grow and develop the principles of populist architecture in Kendari City. This research is intended to make a simple home prototype for the lower class society with the principles of populist architecture. This research uses research and development methods. Sources of data in this study consisted of primary data sources and secondary data. Data collection techniques are carried out by observation, interviews, and documentation. The data were analyzed by means of the data being reduced, the data presented, and the data being concluded. This research concludes that marginal houses are made with the principles of form follows economics. Economic principles are applied to building materials and building sizes.